Capitalization of Hatred and Mass Mobilization: 2017 Jakarta Gubernatorial Election Case - FAHRIZAL, MOHAMMAD (Jurnal Studi Pemerintahan, 2019)
This paper aims to describe in detail how the capitalization of hatred can effectively be used as a political commodity, especially in terms of mass mobilization to intervene in government policies. By utilizing a theoretical approach of Cherian George, the author tries to analyze the campaign process and the 2017 Jakarta gubernatorial election, which involves a lot of practices of capitalization of hatred - especially by using religious narratives - so that it successfully raises negative views of certain social groups. This study proves that hatred capitalization has profoundly used to mobilize mass and suppress opposing group voters so that certain candidates can achieve a political gain in the election.